Evaluation of Varietal Effect and Different Manure Sources on the Soil Chemical Properties, Growth and Yield of Sweet Potato (lpomea batatas L.) in Ishiagu, Southeastern Nigeria - , J. C. Nwite; , P. O. Okereke; , O. C. Olejeme; , C. I. Keke (Archives of Current Research International, 2015)
The research was conducted at the Research and Teaching Farm of the Federal College of Agriculture, Ishiagu, Southeastern Nigeria, to investigate the effect of manure sources on soil chemical properties, growth and yield of two sweet potato varieties in Ishiagu. A Split-plot in a randomized complete block (RCBD) was used. Two sweet potato varieties (TIS 87/0087 and UMUSOP) constituted the main plot, whereas the amendments that constituted the sub-plots were applied as follows: Moringa leaves ML) at 5 t/ha, Neem Leaves (NL) at 5 t/ha, Poultry dropping (PD) at 10 t/ha, Rice husk dust (RHD) at 10 t/ha, Rice husk ash (RHA) at 10 t/ha, NPK Fertilizer (15:15:15) at 400 kg/ha and 0 t/ha (control). Each of the seven (7) treatments in the sub-plot was replicated three (3) times in each of the main plot. The crop was planted on the spacing of 30 cm x 100 cm inter and intra respectively. Soil chemical properties evaluated were pH, organic carbon, total nitrogen and cation exchange capacity (CEC). The growth and tuber yield parameters measured include: Vine length (cm) and weight of tuber t/ha. The soil amendments showed significant effect on the soil pH, organic carbon, total nitrogen and cation exchange capacity (CEC). The result indicated that application of organic manure significantly (P<0.05) increased the selected soil chemical properties, growth and yield parameters of sweet potato varieties. This study revealed the superiority of organic manure sources in the improvement of some chemical properties of the soil and in production of sweet potato in Southeastern Nigeria.